On the problem of early child development in the psychoanalytic pedagogy of René Arpad Spitz - Vertel, Anton (Berdyansk State Pedagogical University, 2024)
The article explains R. A. Spitz’s psychoanalytic concept of early child development from birth to two years. Special emphasis is made on the problem of preverbal communication, on those phenomena that occur long before the child uses words and acquires language. Stages of development in the concept of R. A. Spitz are levels of increasing complexity in the child’s mental structure. The beginning of each of these successive stages is marked by the emergence of specific affective behavior, which is an indicator of a new phase of development. It is shown that in the concept of R. A. Spitz, the development of a child depends on the consistent development of object relations and the establishment of a libidinous object (the object of attachment and love, which is most often the mother). The stages of development of object relations and the stages of the child’s «Ego»/«Self» development were analyzed: 1. The stage of non-differentiation (from birth to 2-3 months): during the first month of life, the baby does not yet separate himself and the environment. 2. The stage of appearance of the harbinger of the libidinous object (from 2-3 to 7-8 months), which begins with the appearance of a social smile, which is a representation of «Ego»/«Self». 3. The stage of the appearance of the libidinous object (from 7-8 to 15 months), which is characterized by eight-month-old anxiety or separation anxiety (fear of separation) – a natural manifestation of the normal development of a child, which manifests itself at the age of about 8 months. 4. The stage of semantic communication (from 15 months to 2 years). Symbolization and fantasizing appear, thanks to the rapid development of language. Sexual identification begins through sexual differentiation. The main sign of the stage is the appearance of negativism at the verbal and non-verbal level. The article analyzes the phenomenon of «hospitalism» as a consequence of the lack of sensory, emotional and intellectual interactions with the mother (or the person who substitutes her). The disorder has been shown to occur with prolonged separation in case of institutional care, hospitals, and dysfunctional families. It has been demonstrated that maternal deprivation, or incorrect, destructive relationships in the mother-infant dyad can cause disturbances in the development of the infant.
Keywords: psychoanalytic pedagogy; stages of child development; maternal deprivation; hospitalism